2011
DOI: 10.1007/s00595-011-0106-4
|View full text |Cite
|
Sign up to set email alerts
|

Tissue engineered myoblast sheets improved cardiac function sufficiently to discontinue LVAS in a patient with DCM: report of a case

Abstract: Dilated cardiomyopathy (DCM) is a heart muscle disease characterized by progressive heart failure, and is a leading cause of mortality and morbidity. Recently, cellular therapy for end-stage heart failure has been emerging. We herein report a 56-year-old male who received a transplant of autologous myoblast sheets manufactured in temperature-responsive culture dishes. His clinical condition improved markedly, leaving him without any arrhythmia and able to discontinue using a left ventricular assist system and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
189
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 304 publications
(196 citation statements)
references
References 5 publications
2
189
0
2
Order By: Relevance
“…For this reason, we attempted to make small intestinal cell sheets. In previous reports, adhesiveness of cell sheets has proven to have a strong ability to survive within organs as compared with other method of transplantation in vitro [6,41,42]. Cell sheets retained their adhesion molecules consisting of ECM and intercellular adhesion molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, we attempted to make small intestinal cell sheets. In previous reports, adhesiveness of cell sheets has proven to have a strong ability to survive within organs as compared with other method of transplantation in vitro [6,41,42]. Cell sheets retained their adhesion molecules consisting of ECM and intercellular adhesion molecules.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Having such features, cell sheets have been used for ours and a variety of other clinical studies based on new regenerative therapy. Prevention of esophageal stenosis after endoscopic submucosal dissection [5], improvement of heart function against chronic heart dysfunction [6] and improvement of corneal opacity [7] have been performed with human autologous cell sheets as clinical studies in Japan and the outcome in most cases was very favorable.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the promising results in various animal models, there is a clinical study using cell sheet transplantation currently underway. Autologous skeletal myoblast sheet therapy has demonstrated that it is possible to improve cardiac function to such a degree that LVADs are no longer required for patients with dilated cardiomyopathy [20]. …”
Section: Cell Sheet Transplantation In Preclinical and Clinical Studiesmentioning
confidence: 99%
“…In this study, the transplantation of eight sheets containing 25×10 6 cardiomyocytes improved left ventricular ejection fraction compared to sham (53 vs. 38 %), but the number of human cardiomyocytes remaining on the host myocardium 8 weeks after transplantation was very low, indicating that the functional improvement was independent of new muscle mass and due to a paracrine mechanism, a conclusion similarly made in many cell-therapy studies. After a further study in dogs [108], the group reported the first inman-study, in which cell sheets of autologous skeletal myoblasts were transplanted in a patient with idiopathic DCM and prolonged treatment with a left ventricular assist device [109]. Implantation of the cell sheet was associated with a decrease in brain natriuretic peptide plasma levels (marker of heart failure), increase in left ventricular ejection fraction, and removal of the assist device.…”
Section: Approaches For the Use Of Pluripotent Stem Cell Products In mentioning
confidence: 99%